2018
DOI: 10.1186/s12884-018-1666-8
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression and relationship satisfaction in the pregnancy following stillbirth and after the birth of a live-born baby: a prospective study

Abstract: BackgroundExperiencing a stillbirth can be a potent stressor for psychological distress in the subsequent pregnancy and possibly after the subsequent birth. The impact on women’s relationship with her partner in the subsequent pregnancy and postpartum remains uncertain. The objectives of the study were 1) To investigate the prevalence of anxiety and depression in the pregnancy following stillbirth and assess gestational age at stillbirth and inter-pregnancy interval as individual risk factors. 2) To assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 44 publications
2
35
0
1
Order By: Relevance
“…Participants who did become pregnant after the PD reported that they went to emergency services more often in the following pregnancies, out of fear and concern that the PD would recur. Other studies suggest that fear and anguish of a new PD increases visits to healthcare services [15,64,65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants who did become pregnant after the PD reported that they went to emergency services more often in the following pregnancies, out of fear and concern that the PD would recur. Other studies suggest that fear and anguish of a new PD increases visits to healthcare services [15,64,65].…”
Section: Discussionmentioning
confidence: 99%
“…The physical of 18 symptoms include decreased appetite, weight loss [12], insomnia [13], increased chronic diseases, and decreased quality of life [14]. On a psychological level, parents who suffer a PD have a greater predisposition to suffer anxiety, depression [15], post-traumatic stress syndrome [16], and even an increased risk of suicide [17]. In the family environment, the death of a baby modifies family relationships [18] and changes the behavior and type of care for older children [19], varying from overprotection [20] to the distancing of other children and neglect of parental obligations [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous stillbirth is also commonly associated with intense anxiety and fear in the next pregnancy, with some women feeling a lack of confidence in their capacity to maintain a healthy pregnancy (Gravensteen 2018;Meaney 2017;Mills 2014). The fear of experiencing another loss may further increase risk, as stress during pregnancy has also been associated with adverse pregnancy outcomes, such as preterm birth (Dunkel Schetter 2011; Van den Bergh 2005) and low birthweight (Baibazarova 2013; Dunkel Schetter 2011; Su 2015; Van den Bergh 2005), possibly mediated by placental function (O'Donnell 2009).…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…This may lead to dysregulation of family life leading to psychological and other problems in subsequently born children [8]. Mothers who have experienced stillbirth are more likely to report symptoms of anxiety (22.5%) and depression (19.7%) during subsequent pregnancies compared to women whose babies are born alive [9]. In addition, poor and emotional health outcomes have been associated with adverse health outcomes (i.e., poor self-rated health) which can affect physical well-being in subsequent pregnancies [5].…”
Section: Introductionmentioning
confidence: 99%